If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(3x + 9) = 15 + -7x Reorder the terms: -8(9 + 3x) = 15 + -7x (9 * -8 + 3x * -8) = 15 + -7x (-72 + -24x) = 15 + -7x Solving -72 + -24x = 15 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -72 + -24x + 7x = 15 + -7x + 7x Combine like terms: -24x + 7x = -17x -72 + -17x = 15 + -7x + 7x Combine like terms: -7x + 7x = 0 -72 + -17x = 15 + 0 -72 + -17x = 15 Add '72' to each side of the equation. -72 + 72 + -17x = 15 + 72 Combine like terms: -72 + 72 = 0 0 + -17x = 15 + 72 -17x = 15 + 72 Combine like terms: 15 + 72 = 87 -17x = 87 Divide each side by '-17'. x = -5.117647059 Simplifying x = -5.117647059
| 14x+8y=135 | | 15-3y=2y+6 | | 6x-3x+x-3+5x= | | -[9z-(17z+1)]=1+(7z+5) | | 8+7k=3k | | 3(8x+3)-2=22x+15 | | -32y+7=-18 | | (2xy-(3(x^2)))dx+((x^2)+y)dy=0 | | 5+7y-21y= | | 15p+7=qforp | | 9+6(6x-7)=-8-6(6x+4) | | 9x+7y=229 | | 5x^2+4x+5=5 | | 0.19x+0.7(x-4)=.01(2x-1) | | 5x^2+4c+5=5 | | 13-14= | | 33y^10+18y^6=0 | | -18-(-4)= | | -4-7s=5s+8 | | 65y^10+30y^7=0 | | 5x^2+23x-38=4 | | -8-(-1+6)= | | 9=A+b-c | | 2y+5=4y | | 7k+NJ=Jr+4m+3form | | y^2+12x=2y-13 | | 4(2x+5)=13x+17-5x+3 | | (2z-7)-7= | | 4x+4y=-22 | | -3m-2=37 | | 8s^2+2s=0 | | -6+10w=4w |